DNA Methylation at the Novel CpG Sites in the Promoter of MED15/PCQAP Gene as a Biomarker for Head and Neck Cancers. Issue 9 (January 2014) - Ovchinnikov, Dmitry A.; Wan, Yunxia; Coman, William B.; Pandit, Pratibala; Cooper-White, Justin J.; Herman, James G.; Punyadeera, Chamindie
Head and neck cancers (HNCs) represent a significant and ever-growing burden to the modern society, mainly due to the lack of early diagnostic methods. A significant number of HNCs is often associated with drinking, smoking, chewing beetle nut, and human papilloma virus (HPV) infections. We have analyzed DNA methylation patterns in tumor and normal tissue samples collected from head and neck squamous cell carcinoma (HNSCC) patients who were smokers. We have identified novel methylation sites in the promoter of the mediator complex subunit 15 ( MED15/PCQAP ) gene (encoing a co-factor important for regulation of transcription initiation for promoters of many genes), hyper methylated specifically in tumor cells. Two clusters of CpG dinucleotides methylated in tumors, but not in normal tissue from the same patients, were identified. These CpG methylation events in saliva samples were further validated in a separate cohort of HNSCC patients (who developed cancer due to smoking or HPV infections) and healthy controls using methylation-specific PCR (MSP). We used saliva as a biological medium because of its non-invasive nature, close proximity to the tumors, easiness and it is an economically viable option for large-scale screening studies. The methylation levels for the two identified CpG clusters were significantly different between the saliva samples collected from healthy controls and HNSCC individuals (Welch's t -test returning P < 0.05 and Mann–Whitney test P < 0.01 for both). The developed MSP assays also provided a good discriminative ability with AUC values of 0.70 ( P < 0.01) and 0.63 ( P < 0.05). The identified novel CpG methylation sites may serve as potential non-invasive biomarkers for detecting HNSCC.